Wrecker - Hiaasen, Carl (Alfred A. Knopf, 2023)
"Valdez Jones VIII calls himself Wrecker because his great-great-great-great-great-grandfather salvaged shipwrecks for a living. So is it destiny, irony, or just bad luck when Wrecker comes across a speedboat that has run hard aground on a sand flat? The men in the boat don't want Wrecker to call for help--in fact, they'll pay him to forget he ever saw them. Wrecker would be happy to forget, but he keeps seeing these men all over Key West--at the marina, in the cemetery, even right outside his own door. And now they want more than his silence--they want a lookout. He'll have to dive deep into their shady dealings to figure out a way to escape this tangled net. . . ." --